2010
DOI: 10.1371/journal.pone.0011592
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Is Low on the Value Ladder of Rats: Possible Evidence for Resilience to Addiction

Abstract: BackgroundAssessing the relative value of cocaine and how it changes with chronic drug use represents a long-standing goal in addiction research. Surprisingly, recent experiments in rats – by far the most frequently used animal model in this field – suggest that the value of cocaine is lower than previously thought.Methodology/Principal FindingsHere we report a series of choice experiments that better define the relative position of cocaine on the value ladder of rats (i.e., preference rank-ordering of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
194
6
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(230 citation statements)
references
References 78 publications
27
194
6
3
Order By: Relevance
“…Indeed, we recently found that most rats trained to self-administer both food and methamphetamine prefer the food pellets (Caprioli and Shaham, unpublished data). These data confirm previous results of Ahmed and Lenoir that the majority of rats trained for cocaine self-administration strongly prefer an alternative non-drug food reward (saccharin solution) (Ahmed et al, 2013;Cantin et al, 2010;Lenoir et al, 2007). A question for future research is whether both resistance to punishment and preference for food over methamphetamine would be reversed in rats classified as 'addicts' following months of drug self-administration in the DSM-based addiction model developed in Bordeaux (Deroche-Gamonet and Piazza, 2014;Piazza and DerocheGamonet, 2013).…”
Section: Resistance To Punishment After Methamphetamine and Food Selfsupporting
confidence: 92%
“…Indeed, we recently found that most rats trained to self-administer both food and methamphetamine prefer the food pellets (Caprioli and Shaham, unpublished data). These data confirm previous results of Ahmed and Lenoir that the majority of rats trained for cocaine self-administration strongly prefer an alternative non-drug food reward (saccharin solution) (Ahmed et al, 2013;Cantin et al, 2010;Lenoir et al, 2007). A question for future research is whether both resistance to punishment and preference for food over methamphetamine would be reversed in rats classified as 'addicts' following months of drug self-administration in the DSM-based addiction model developed in Bordeaux (Deroche-Gamonet and Piazza, 2014;Piazza and DerocheGamonet, 2013).…”
Section: Resistance To Punishment After Methamphetamine and Food Selfsupporting
confidence: 92%
“…Importantly, a 10-min intertrial interval was used here, as well as in all previous experiments from this laboratory, because it takes ∼ 10 min for the locomotor effects of the testing dose of cocaine (0.25 mg) or heroin (0.01 mg) to dissipate (Cantin et al, 2010;Lenoir et al, , 2013. As a result, this procedure defines a setting where choosing under the drug influence is not possible or only minimal, even if rats happen to choose cocaine on most trials.…”
Section: General Behavioral Proceduresmentioning
confidence: 99%
“…There is growing awareness that such lack of options may limit the validity of this research for understanding drug addiction as a drug use disorder (Ahmed, 2005(Ahmed, , 2010Ahmed et al, 2013;Alexander and Hadaway, 1982;Cantin et al, 2010;Caprioli et al, 2015b;Carroll et al, 1989;Kerstetter et al, 2012;Le Sage, 2009;Lenoir et al, , 2013Liu and Grigson, 2005;Perry et al, 2013;Thomsen et al, 2013;Tunstall and Kearns, 2013;Zernig et al, 2013). Indeed, when there is no valuable alternative to the drug, drug self-administration may merely reflect a normal reaction to the lack of choice as opposed to reflecting a disordered behavior caused by an underlying dysfunction (Ahmed, 2010;Ahmed et al, 2013;Hyman and Malenka, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, this has yet to be converted into new therapeutic approaches. 13 Here we consider what may protect nonclinical voice hearers, inspired by similar studies in addiction, 14 oncology, 15 and infectious diseases 16,17 : there are individuals who are resilient despite similar exposure to risk factors as individuals who become ill.…”
Section: Introductionmentioning
confidence: 99%